Heleodromia Haliday newly recorded from China with descriptions of two new species (Diptera: Empidoidea) - Liu, Xiaoyan; Wang, Jinjing; Yang, Ding (Zootaxa, 2012)
The genus Heleodromia Haliday is recorded from China for the first time with the following three species belonging tothe subgenus Heleodromia: Heleodromia (Heleodromia) didyma sp. nov., H. (H.) helanshana sp. nov., and H. (H.) immaculata Haliday. A key to the known species of Heleodromia from China is presented.